Probability generating function.

  • Thread starter nikki92
  • Start date
  • #1
40
0

Main Question or Discussion Point

For any integer valued RV X Summation n=0 to infinity of s^n P(X=<n) = (1-s)^-1 * Summation k=0 to infinity of P(x=k)s^k


Why does Sum k=0 to infinity P(x=k)s^k = sum n=0 to infinity of P(X=< n)
 

Answers and Replies

  • #2
34,366
10,438
$$\sum_{n=0}^{\infty} s^n P(X\leq n) = \sum_0^{\infty} s^n \sum_{k=0}^n P(X=k)$$
You can re-write this double sum and use k as primary index. The inner sum (over n) has an explicit formula then, and you get the correct result.
 

Related Threads on Probability generating function.

  • Last Post
Replies
2
Views
2K
Replies
3
Views
4K
Replies
1
Views
3K
Replies
4
Views
17K
Replies
2
Views
4K
Replies
1
Views
1K
Replies
2
Views
566
Replies
22
Views
1K
Top